(untitled) (VETERINARIA, 2021)
The Department of Veterinary State and Forensic Medicine of the Faculty of Veterinary Medicine, University of Sarajevo, received a request for ichthyofaunal damage assessment in the fishing area of rivers, tributaries and lakes in the municipality of Konjic. The damage was caused by cleaning activities, removal of sediment from the riverbed and damage repair activities on the banks of the upper course of the Neretva River, which was carried out with certain irregularities that are not in accordance with the granted permit. Such irresponsible human activities inevitably have an impact on the living world of the aquatic ecosystem and often cause long-term harmful consequences. Through the presentation of this case, our main goal is to present the different types of harmful consequences resulting from such activities as well as the methodology of their calculation. In addition, the paper also points to violations of certain laws and bylaws governing this segment.